Los mecanismos de modalización en las oraciones condicionales no reales: del latín a los romances (con especial atención al castellano) - Nowikow, Wiaczesław (Rome and Iberia : Inspirations and Connections throughout History, 2021)
The aim of this paper is to analyze the mechanism of modalization in conditional sentences during the evolution from Latin to Romance languages. The analysis is realized with special attention to Spanish. The modal modification of the transmitted contents is connected with two factors (mood and tense): 1. The modal value of the Subjunctive mood and 2. The temporal translocation of the Latin and Romance tenses. Some Romance languages (e.g. Spanish, Portuguese and Italian) represent mostly the first solution. Others languages (e.g. French, Occitan and Catalan) select exclusively or principally the second possibility. Nevertheless, the temporal translocation connected with the change of the modal contents is possible in all Romance languages.